SCREENING AND AWARENESS OF GLAUCOMA IN FIRST DEGREE RELATIVES IN GLAUCOMA PATIENTS ATTENDING DEPARTMENT OF OPHTHALMOLOGY OF A TERTIARY CARE HOSPITAL - Dahal, Polina; Acharya, Amrit; Lamichhane, Kripesh; Subedi, Anil; Khanal, Niharika; Sah, Ranjeet; Singh Thakuri, Rabindra; Adhikari, Rishikanth (Journal of Chitwan Medical College, 2024)
Background: Glaucoma is the most common cause of irreversible blindness worldwide. Family history of Glaucoma is one of the major risk factors for glaucoma predisposition. Presence of family history of glaucoma is an important indication for screening of glaucoma. The main objective of this study was to determine the prevalence of glaucoma in first degree relatives and also to assess the level of awareness among them. Methods: It was the hospital based cross-sectional study designed to screen, examine and diagnose glaucoma patient’s first-degree relatives attending the outpatient department of Chitwan medical college from 30th March 2023 to 29th march 2024. All first-degree family members of glaucoma patients; who accompanied them to the glaucoma clinic, underwent a full ocular examination. Along with the general ophthalmological examination, the optic disc evaluation was done with slit lamp using 90D volk lens and intraocular pressure was measured with Goldmann applanation tonometry. Diagnosis was then defined as per ISGEO classification. Results: Among 115 participants 22 (19.1%) were POAG suspect, 8 (7.0%) were primary open angle glaucoma, 24 (20.9%) were PACG suspect, 2 (1.7%) were chronic angle closure glaucoma and 59 (51.3%) had no any signs of glaucoma. Conclusions: Ocular examination of the first-degree relatives accompanying glaucoma patients helps to screen a remarkable number of people with glaucoma and it can be an easy way to screen glaucoma cases in hospital settings.